Effect of feeding patterns on growth and nutritional status of children aged 0-24 months: A Chinese cohort study - Tian, Qianling (PLoS One, 2019)
OBJECTIVE: This study was aimed to examine the effect of feeding patterns on growth and nutritional status of children aged 0~24 months. METHODS: We conducted a cohort study with an initial sample of 927 children. Considering the follow-up losses, 903, 897, 895, 897, 883, 827 and 750 children were followed up at 1, 3, 6, 8, 12, 18 and 24 months, respectively. Children were grouped according to exclusive breastfeeding (EBF) duration in the first 6 months: (1) never EBF; (2) EBF ≤ 3 months: EBF ≤ 3 months and stopped BF after 3 months or EBF ≤ 3 months and BF = 6 months or EBF ≤ 3 months and BF after 3 months, had formula and/or solids; (3) EBF for 3 ~ 6 months: BF < 3 months and EBF for 3 ~ 6 months or EBF for 3 ~ 6 months and BF < 3 months, had formula and/or solids; (4) EBF = 6 months. We used Z-scores to evaluate the growth and nutritional status of children, used the generalized estimation equation to compare the difference between feeding patterns. RESULTS: The generalized estimation equation results showed that Weight-for-age Z-score (WAZ), Length-for-age Z-score (LAZ), and Weight-for-length Z-score (WLZ) in different feeding patterns had statistical significance. The WAZ in EBF for 6 months group was higher in the first 8 months, in never EBF group was higher after 12 months old; the LAZ in EBF for 6 month group was lower than other groups; the WLZ in EBF for 6 months group was higher than EBF for 3 ~ 6 months group. The EBF ≤ 3 months group had higher underweight, stunting, and wasting rates. The EBF for 6 months had a higher stunting rate; the never EBF and EBF for 6 months groups had higher overweight and obesity rates. CONCLUSIONS: In conclusion, different feeding patterns affect growth and nutritional status in children, so proper guidelines should be implemented to improve nutritional status and promote the growth of children.